A community considers a Family Justice Center: perspectives of stakeholders during the early phases of development. Issue 2 (8th April 2014) - E. Murray, Christine; White, Jacquelyn; Nemati, Hamid; Chow, Anthony; Marsh, Allison; Edwards, Samantha
Abstract : Purpose: – Family Justice Centers, or "one-stop shops" that enable domestic violence victims to access a range of services at one location, are becoming increasingly common. However, there is a limited body of research examining the outcomes and planning processes of these Centers. The early phases of planning Centers are critical to their initial and ongoing success. The purpose of this paper is to discuss these issues. Design/methodology/approach: – In total, 15 stakeholders in a community in the early phases of planning a Center were interviewed. Findings: – Content analysis procedures were used to identify themes related to participants' ideas about what the Family Justice Center should look like (e.g. services to include and perceived benefits and challenges for the Center), the steps required for planning it (e.g. identifying the purpose of the Center, getting key people involved, and building collaborations), and desired technologies. Originality/value: – This paper is the first known research effort to examine the early phases of development in constructing a Family Justice Center.